Which food outlets are important for nutrient-dense-porridge-flour access by the base-of-the-pyramid consumers? Evidence from the Informal Kenyan settlements - Koech, Kevin K.; Chege, Christine Gacheri Kiria; Bett, Hillary Kiplangat (MDPI, 2022)
Many Kenyan base-of-the-pyramid (BoP) consumers—defined as the poorest two-thirds of the economic human pyramid—remain food insecure, despite the availability of nutrient-dense foods in the market. This study reveals how effective marketing strategies can strengthen food security among BoP consumers through increased access to nutritious foods such as nutrient-dense porridge flour. Nutrient-dense porridge flour refers to a multi-composite porridge flour composed of diverse nutritious ingredients that are necessary to achieve a healthy diet. The main objective of the study was to determine the most effective channel for making nutrient-dense porridge flour available to BoP consumers. Data were collected through a cross-sectional survey in Kawangware, Nairobi County, using a multistage sampling design and a sample size of 603, via structured questionnaires. A multivariate Probit (MV-Probit) model was used to analyze the most effective channel for providing nutrient-dense flour to BoP consumers. The study results show that the most common outlets used to access this flour were supermarkets (51.08%), followed by cereal stores (25.54%). According to previous studies, using appropriate marketing strategies leads to increases in the uptake and consumption of nutritious products in informal urban settlements among developing countries. Consequently, policies and interventions targeting BoP consumption of nutritious products toward reducing food and nutrition insecurity in informal urban settlements should be based on appropriate marketing strategies that consider the institutional factors and significant household characteristics of the BoP communities.